Robotic construction: experiments with robotic arms and drones for the building construction industry - Silva, N.; Eloy, S. (Sustainability and Automation in Smart Constructions. Proceedings of the International Conference on Automation Innovation in Construction (CIAC-2019), 2020)
This paper aims to explore the possibilities that robotic technologies, namely robotic arms and drones, bring to architecture and to the construction sector. The developed research was based in a literature review regarding drones, ro-botic arms and hybrid automatic construction solutions. The paper starts by presenting a brief resume about the robotic technologies that are presently used, mainly in academic research, to assemble construction elements. We then analyse eight case studies of construction performed with drones and robotic arms in order to explore different approaches to the robotic construc-tion. The advances in robotic construction are visible and growing every year. According to experts, robotic construction will be introduced in the construction industry in a hybrid way by a collaboration between man and machine and not as total substitution of human labour.